Pelatihan Pembuatan Web Organisasi Pada Jaringan Internet Untuk Remaja Di RT 014/RW 01 Gg. Rambutan Jagakarsa Kota Jakarta Selatan - Dwi Sidik Permana; Boy Firmansyah (Jurnal Pengabdian Teratai, 2020)
The development of science in today's era has increased so rapidly. The increasing need for information encourages people to develop new technologies so that data and information processing can be done easily and quickly. To make things easier, of course not only using human labor, but also using modern technology, for example by utilizing internet technology. Many teenagers are competing to install internet networks to be able to enjoy the convenience of obtaining information via the internet, one of which is RT 014 / RW 01 Gg. Rambutan Jagakarsa, South Jakarta City. Youth at RT 014 / RW 01 Gg. Rambutan Jagakarsa, Jakarta City. Currently, most teenagers have used the Internet in their environment but the use of this Internet network is still not optimal due to the ability to utilize information technology. This can be seen from the absence of blog sites or websites. By looking at the benefits that can be obtained from a youth association website at RT 014 / RW 01 Gg. Rambutan Jagakarsa, South Jakarta City as a medium of learning media, it is necessary to hold web development training on computer networks to create and manage youth websites at RT 014 / RW 01 Gg. Rambutan Jagakarsa, South Jakarta City